1987
DOI: 10.1557/jmr.1987.0768
|View full text |Cite
|
Sign up to set email alerts
|

X-ray photoemission spectroscopy of the 90 K superconductor Ba2YCu3O7−δ

Abstract: The x-ray photoemission spectroscopic (XPS) data from different pelletized samples of the 90 K superconductor Ba2YCu3O7 _ s (where S~0.2) have been obtained. The valence band spectrum (recorded at 300 and 170 K), which is composed of contributions from both the Cu 3c? and O 2p levels, is compared with the full potential linearized augmented plane wave (FLAPW) calculated electronic density-of-states (DOS) reported by Massidda et al. and Mattheiss and Hamann. The experimental data indicate a relatively low DOS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Based on the photoemission studies by Iqbal et al, it is suggested that this peak arises from the absorption of hydrides, water, and CO 2 on surface. 44 The Pr M 45 -edge and Cu L 23 -edge x-ray-absorption nearedge-structure x-ray-fluorescence-yield spectra for a series of (Dy 1Ϫx Pr x )Ba 2 Cu 3 O 7Ϫ␦ compounds in the energy range 925-960 eV are shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the photoemission studies by Iqbal et al, it is suggested that this peak arises from the absorption of hydrides, water, and CO 2 on surface. 44 The Pr M 45 -edge and Cu L 23 -edge x-ray-absorption nearedge-structure x-ray-fluorescence-yield spectra for a series of (Dy 1Ϫx Pr x )Ba 2 Cu 3 O 7Ϫ␦ compounds in the energy range 925-960 eV are shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of their X-ray photoemission studies, Iqbal et al . suggested that these peaks are due to absorption of hydrides, water, and CO 2 on the surface …”
Section: Resultsmentioning
confidence: 99%
“…On the basis of their X-ray photoemission studies, Iqbal et al suggested that these peaks are due to absorption of hydrides, water, and CO 2 on the surface. 24 In Figure 9 are shown the Cu L 23 -edge X-ray-absorption nearedge-structure X-ray-fluorescence-yield spectra for the series of (Hg 0.5 Pb 0.5 )(Sr 2-x Ba x )(Ca 0.7 Y 0.3 )Cu 2 O 7-δ samples with x ) 0-0.5. As noted from Figure 9, the Cu L 23 -edge absorption spectra are asymmetric with two shoulders at the high-energy side of the main peaks.…”
Section: Resultsmentioning
confidence: 99%
“…This change is related to a spectral weight transfer of states from the UHB to doping-induced hole states near the Fermi level. 65 Figure 8 presents the PrM 45 -edge and CuL 23 -edge x-rayfluorescence-yield spectra for the series of (La 1Ϫx Pr x )Ba 2 Cu 3 O z compounds with xϭ0, 0.1, 0.2, 0.3, 0.5, and 0.6 in the photon energy range of 920-960 eV. As marked on the top of Fig.…”
Section: Resultsmentioning
confidence: 99%